Edible Film with Antioxidant Capacity Based on Salmon Gelatin and Boldine - Bustos-Cerda, R; Venegas-Yazigi, D; Venegas-Yazigi, D; Gutierrez-Cutino, M; Gutierrez-Cutino, M; Lopez-Angulo, D; Matiacevich, S (Academic Press, 2017)
Salmon gelatin and boldine as a natural antioxidant were used to prepare edible films by a cold casting method. The concentration of each component was optimised by applying a Box-Behnken experimental design (BBD) with the goal of maximising radical scavenging capacity of film forming suspensions (FFS) measured by the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical assay. The results showed synergistic effect between gelatin and boldine for the antioxidant capacity (radical scavenging of over 80%) and antimicrobial activity of gelatin against Escherichia coli ATCC 25922 and Listeria monocytogenes ISP 6508. The release of boldine into the food simulant was faster for films containing 2 % gelatin than for those containing 4 %. Kinetic data for boldine release from films fitted to the Weibull model (r = 0,99). Possible molecular interactions between gelatin and boldine were observed in the FTIR spectrum of the composite films. Within the range of 1638 to 1628 cm-1 a strong interference caused by boldine in the hydrogen bonding between water and imide residues was observed. Owing to the simultaneous antioxidant and antimicrobial activities displayed for the gelatinboldine films, there is potential for application in the preservation of some perishable fresh food such as fish, meat and cheese. © 2016 Elsevier Ltd